Tracking Groundwater Levels Using the Ambient Seismic Field. Issue 13 (7th July 2018) - Clements, Timothy; Denolle, Marine A.
Abstract: Aquifers are vital groundwater reservoirs for residential, agricultural, and industrial activities worldwide. Tracking their state with high temporal and spatial resolution is critical for water resource management at the regional scale yet is rarely achieved from a single type of groundwater data. Here we show that variations in groundwater levels can be mapped using perturbations in seismic velocity ( dv/v ). We measure dv/v in the San Gabriel Valley, California, from cross correlation of the ambient seismic field. dv/v reproduces the groundwater level changes that are marked by the multiyear depletions and rapid recharges, typical of California's cycles of droughts and floods. dv/v correlates spatially with vertical surface displacements and deformation measured with the Global Positioning System (GPS). Our results successfully predict the volume of water lost in the San Gabriel Valley during the 2012–2016 drought and thus provide a new, complementary approach to monitor groundwater storage. Plain Language Summary: The largest reservoir of freshwater worldwide is stored beneath our feet in groundwater aquifers. Monitoring the availability of water stored in the ground is critical for communities that are susceptible to drought, as groundwater can supplement a lack of surface fresh water. We propose a new way to monitor groundwater levels in aquifers using weak seismic waves repeatedly generated by the ocean, wind, and human activities. We exploit the fact that the speed of seismic waves is sensitive to the amount of the water in the ground. Using a network of seismometers, we measure the change in seismic velocity throughout the San Gabriel Valley Basin, California. We find that with the change in seismic velocity we can estimate the flux of water in the San Gabriel Valley over the last three droughts and subsequent recoveries that have affected Southern California over the last two decades. These results provide a new approach to monitor groundwater storage. Key Points: Groundwater levels in the San Gabriel Valley Basin, California, reach all‐time low after 2011‐2016 drought Seismic velocities respond linearly with drawdown and recharge of ground water aquifer Change in seismic velocity change used to estimate change in groundwater storage